2016
DOI: 10.1111/jth.13486
|View full text |Cite
|
Sign up to set email alerts
|

Poor comparability of coagulation screening test with specific measurement in patients receiving direct oral anticoagulants: results from a multicenter/multiplatform study

Abstract: Background Prothrombin time (PT) and activated partial thromboplastin time (APTT) have been proposed to measure the effect of oral anti-activated factor X (FXa) or anti-activated FII drugs, respectively. Aims To evaluate the relationships and responsiveness of PT and APTT versus direct oral anticoagulant (DOAC) concentrations measured with specific coagulation tests performed with different platforms in four Italian anticoagulation clinics. Methods Six hundred and thirty-five patients with atrial fibrillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 32 publications
3
65
0
2
Order By: Relevance
“…Via inhibition of thrombin, factor Xa, but also of factors IXa, XIa, XIIa, tissue plasminogen activator (tPA), trypsin, plasmin, urokinase and kallikrein, ATIII acts as a physiologic anticoagulant[28]. It is well known that PT is prolonged by a series of conditions, including direct acting anticoagulants (among them argatroban, dabigatran, rivaroxaban, apixaban, edoxaban)[29] and intake of vitamin K antagonists[30], vitamin K deficiency[31], coagulation factor deficiency, lupus anticoagulans[32], polycitemia vera[33]. Similarly, it was shown that factor VII deficiency is frequent in patients with infections, neoplasia, trauma, nephrotic syndrome, left heart failure, penicillin intake and clearly in patients under vitamin K dependent anticoagulation[34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Via inhibition of thrombin, factor Xa, but also of factors IXa, XIa, XIIa, tissue plasminogen activator (tPA), trypsin, plasmin, urokinase and kallikrein, ATIII acts as a physiologic anticoagulant[28]. It is well known that PT is prolonged by a series of conditions, including direct acting anticoagulants (among them argatroban, dabigatran, rivaroxaban, apixaban, edoxaban)[29] and intake of vitamin K antagonists[30], vitamin K deficiency[31], coagulation factor deficiency, lupus anticoagulans[32], polycitemia vera[33]. Similarly, it was shown that factor VII deficiency is frequent in patients with infections, neoplasia, trauma, nephrotic syndrome, left heart failure, penicillin intake and clearly in patients under vitamin K dependent anticoagulation[34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…However, overall of 26 patients who had rivaroxaban concentrations less than 90 ng/mL, 20 had prolonged PT or aPTT or both. In addition, the extent of prolongation of both PT and aPTT correlated poorly with rivaroxaban concentration limiting their use as a clinical predictor of anticoagulant intensity as previously observed . In the Einstein studies, the mean trough level of rivaroxaban was 32 ng/mL .…”
Section: Discussionmentioning
confidence: 71%
“…This observation opens the question about the importance of laboratory testing in emergency clinical conditions to address appropriate treatments. As previously shown [21], global coagulation tests such as PT and aPTT are not useful to quantify DOAC activity, while specific tests (anti-Xa, dTT, ecarin test) are available and easily adaptable on most commercial coagulation platform. Despite the increasing consensus on the need for DOAC measurement in specific clinical conditions, our study shows a low rate of specific drug measurements in emergency situations, highlighting an urgent need for their implementation in each hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory tests included: blood cell count, liver enzymes (AST, ALT), renal function (creatinine clearance calculated using the Cockcroft-Gault formula), coagulation screening tests (PT and aPTT), and specific DOAC measurements. DOACs levels, expressed as drug concentration equivalent (ng/ml), were measured with diluted thrombin time (dTT) or ecarin chromogenic assay (ECA) calibrated for dabigatran and specific anti-factor X activated (FXa) assays calibrated for apixaban, edoxaban, and rivaroxaban [12,21,22]. All tests were performed locally, and each investigator made decision on whether to perform laboratory or not.…”
Section: Data Collectionmentioning
confidence: 99%